2021
DOI: 10.1111/jam.15154
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of metagenomic data revealed consistent changes of gut microbiome structure and function in inflammatory bowel disease

Abstract: Aims: To reveal the consistency and discrepancy in the gut microbial structure and function in inflammatory bowel disease (IBD) patients from different regions. Methods and Results: Gut microbes, antibiotic resistance genes (ARGs) and virulence factors genes (VFGs) were analysed using metagenome data from three cohorts. The abundance of Escherichia coli extensively increased in IBD patients, whereas Subdoligranulum unclassified decreased dramatically in IBD patients from three countries. Escherichia coli showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Also, IBD phenotype is known to be associated with microbiome dysbiosis which led to upregulation of antibiotic resistance [64], a condition also observed in GW-CMI veterans [65]. We have shown a direct association between gastrointestinal, systemic and neuronal inflammation observed in GW-CMI pathology and diversity of AGFs and resistant drug classes in a mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…Also, IBD phenotype is known to be associated with microbiome dysbiosis which led to upregulation of antibiotic resistance [64], a condition also observed in GW-CMI veterans [65]. We have shown a direct association between gastrointestinal, systemic and neuronal inflammation observed in GW-CMI pathology and diversity of AGFs and resistant drug classes in a mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…Lachnoclostridium is associated with the production of short-chain fatty acids in the gut ( 54 ), and its significant decrease in DHD calves may be related to the significant changes in unsaturated fatty acid metabolism pathways. Subdoligranulum has also been found to be significantly decreased in a lot of intestinal diseases ( 55 , 56 ). In this study, the correlation network analysis showed that DHD was associated with changes in the relevant structure and possible interaction structure of the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Although the energy source and mechanism of Subdoligranulum and its involvement in dyslipidemia are unclear, it is known to produce butyrate, which improves lipid metabolism ( 39 , 40 ). A clinical study in Taiwan and China has reported that Subdoligranulum is depleted in patients with inflammatory bowel disease, suggesting that it may be a helpful bacteria ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%